Boron nitride nanotubes reinforced polycarbonate nanocomposites. (September 2019) - Guan, Jingwen; Derdouri, Abdessalem; Ashrafi, Behnam; Benhalima, Abdelkader; Kim, Keun Su; Daroszewska, Malgosia; Simard, Benoit
Graphical abstract: Highlights: Boron nitride nanotubes are integrated into PC matrix through solvent process. OH and NH2 functionalized BNNTs have improved compatibility with PC matrix. Improved properties of BNNT-PC nanocomposites have been observed. Abstract: Surface functionalized boron nitride nanotubes (f-BNNTs) with hydroxyl (OH) and amino (NH2 ) groups are employed as a nanofiller to reinforce polycarbonate (PC), a resin that has widely been used where a combination of transparency and high energy absorption is required, such as in armor, automotive and display technologies. To improve the interfacial compatibility of BNNTs with the PC matrix, BNNTs are treated with bromine in water inducing BN bond cleavage and subsequent formation of OH and NH2 functional groups on BNNT-surfaces. Samples of 1, 2 and 4 wt% f-BNNT/PC nanocomposite are prepared in a mixture of chloroform and dimethylformamide (DMF). The resulting f-BNNT/PC nanocomposites are processed in two ways: thin film formation from the powder by using a hot-press and plaque formation through melt-mixing-extrusion and compression molding techniques, respectively. The thermal and mechanical properties of the f-BNNT/PC nanocomposites are evaluated and compared with those of neat PC. They exhibit about 4∼8 °C improvement in thermal stability and over 30 °C higher in anti-oxidation than those of the neat PC. The testing result reveals that the f-BNNT/PC nanocomposite at 1 wt% loading achieves 39% increase in tensile toughness relative to the neat PC. Young's modulus has an improvement by 13% (1 wt%) and 31% (4 wt%), respectively, from the thin-film samples; while about 2% and 13% improvements are observed from the extruded coupons at the same f-BNNT loadings. The transparency of the thin films is shown to decrease with the increase of f-BNNT loading.